Pengembangan Media Pembelajaran Berbasis Web “Levietech” Dengan Model Pbl Untuk Meningkatkan Hasil Belajar Siswa Pada Elemen Sistem Komputer - Muhammad Irvan Maulana; Rindu Puspita Wibawa (CV. SINAR HOWUHOWU, 2026)
Computer System learning in Vocational High Schools (SMK), which is often abstract, motivated this research to develop an interactive website-based learning media named